Case report: Post-streptococcal pustulosis after subcutaneous injection of secukinumab - Lang, Xiaoqing; Bi, Hongmei; Zhang, Yingjie; Cui, Hongzhou; Liu, Hongye; Ren, Ling; Dang, Yao; Guo, Shuping (Frontiers in Medicine, 2023)
An acute diffuse pustular eruption occurred in a patient after secukinumab injection and then the clinical presentation has been related to streptococcus infection after it has been isolated from throat swabs. Pustulosisacuta generalisata was definitively diagnosed. Antibiotic treatment had a poor effect, but the response to glucocorticoids was better.